Representasi Nilai-nilai Kehidupan dalam Novel Ine Pare Karya F. Rahardi - Larasati, Maria Marietta Bali (Retorika: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2021)
The purpose of the study was to discover and describe the values in F. Rahardi's novel Ine Pare. The approach used in this study is a qualitative approach with the techniques used is non-statistical in the sense of analyzing not using numbers. The theory used is value theory. The results of this study show that the values contained in the novel Ine Pare by F. Rahardi are as follows: 1) moral values include two values: positive moral values and negative moral values. Positive moral values include: the values of honesty, the value of courage, patience, and hard work, while negative moral values include: dishonest values, prejudice, anger, and revenge, 2) Religious values include: believing in God, gratitude, 3) social values include: mutual help, willingness to sacrifice, 4) aesthetic values, 5) cultural values, 6) practical values, and 7) hedonic values.